Road for Cultural Heritage : Policy Note on Cultural Heritage and Infrastructure Development in Timor-Leste - World Bank (Washington, DC, 2014)
The purpose of this Policy Note is to survey Timor-Leste's cultural heritage in relation to infrastructure development and offer policy options for conserving and developing cultural heritage assets, particularly in relation to sustainable tourism. Infrastructure development can expose cultural heritage assets to new pressures that require new and/or improved measures for conservation. Equally, such development can unlock the potential of cultural heritage assets to provide opportunities for sustainable social and economic benefits for communities. As Timor-Leste makes major investments in its infrastructure in the coming years, it has an opportunity to maximize the benefits of its rich cultural heritage and minimize the risks of damage to important cultural heritage sites. Timor-Leste's cultural heritage is now subject to an unprecedented exposure to the impacts of infrastructure development. From 2008 to 2012, the national budget expanded fivefold, and the 2012 budget allocated 48 percentage of spending for infrastructure, chiefly electricity, roads and the development of the 'Tasi Mane' area petroleum infrastructure. The legal framework for safeguarding cultural heritage and for promoting sustainable development based on the cultural value of these sites is, however, still embryonic. In this context, adapting policy to best conserve and develop Timor-Leste's unique cultural heritage is crucial.